ANALYSIS OF INNOVATIVE ACTIVITIES OF COMPANIES IN DEVELOPED COUNTRIES (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article describes the innovative products offered to the world markets by large companies operating in developed countries, as a result of which companies and investments in countries, and provides relevant analysis and recommendations on this topic.